Однодомность и ненаркотичность Cannabis sativa L. как новые составные систематики современной культуры - Вировец, В.Г.; Лайко, И.М.; Горшкова, Л.М.; Кириченко, А.И.; Мищенко, С.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. Authors appealed to the very eccentric theme of researches, touching position of hemp in biotaxonomy, taking into account its signs as plasticity, economic setting and variation of pharmacy-chemical indexes depending on ecologicallygeographical terms. Methods. Modern confession of hemp in the period of hard agrarian competition, due to ability to give a large income, is investigation of successes of breeding. On the basis of the worked out methodologies the productivity was considerably enhanceable and new drug free varieties are created. Results. In spite of antiquity of the crop, until now doubts are not blown about in relation to belonging of hemp to family of Cannabaceae, as other consider that hemp together with genera of Morus and Humulus nearer to nettle (Urticaceae) or mulberry (Moraceae). Like it there are no single opinion and relatively specifi c division: to attribute a hemp to two kinds — Cannabis sativa L. and Cannabis indica L. or only to the fi rst. On the basis of undertaken studies and created varieties we consider that in the origin of hemp an active role belonged to economic activity of man in certain ecologically-geographical terms that are predominating. Conclusions. The shown out new highly productive drug free varieties testify that a new crop, that on the identity of polymorphological signs presents the new variant of industrial hemp that can be named as Cannabis sativa L. var. non-narcotic Virovets. Keywords: industrial hemp, families and species, breeding, drug free varieties.